كتابات عبد الوهاب المسيري: المداخل الكبرى لولوج فكره: Abdelwahab El-Messiri’s Writings: Major entries to his thought Abstract - مرزاق عبد القادر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2012)
سعت الدراسة إلى تحديد المداخل الكبرى في فكر المسيري، معتقدة أن كتاباته تتأسس على مفاهيم مفاتيح، ويتعذر فهم تفاصيلها ما لم ندركها. من هذه المفاهيم المفاتيح: التوحيد بوصفه يحل إشكالية ثنائية؛ الله، الإنسان؛ فتنجلي من خلال الدراسة صفات الله الخالق، وصفات الإنسان المخلوق. ومنها مفهوم الحلولية؛ وهي الطرف المناقض للتوحيد. ومنها العلمانية الشاملة؛ ولا تعني فصل الدين عن الدولة وحسب، وإنّما فصل كل القيم الإنسانية والأخلاقية والدينية عن حياة الإنسان في جانبيها العام والخاص. The study sought to identify the major entries in El-Messiri’s thought, believing that his writings are based on key concepts, which are necessary to understand it. One of these key concepts is: tawhid (monotheism) which solve the duality of God and man; through clear distinction between God the Creator, and man the created. Pantheism is another key concept: which is the opposite of tawhid. Comprehensive secularism is a third concept and does not mean only separation of religion and state, but separation of all human​​, moral, and religious values, from all sectors o human public life; public private.